Academic dishonesty and its contributing factors among Indonesian first-year college students in the AI era - Gazadinda, Rahmadianty; Qonita, Adhissa; Nuraisyah, Zulfania; Maulana, Aditya Tisna; Yudhistira, Santi; Medellu, Gita Irianda Rizkyani; Rangkuti, Anna Armeini; Fauzia, Jimny Hilda (Jurnal Ilmiah Psikologi Terapan, 2026)
As Artificial Intelligence (AI) increasingly surpasses human capabilities, the potential for its misuse to replace human efforts has become more prominent. Consequently, various disruptions have emerged across multiple domains, including education. In Indonesia, growing concerns about academic dishonesty have emerged alongside the rapid expansion of AI technologies, which may pose new challenges to students’ moral and ethical decision-making both within academic environments and beyond. While the accessibility and ease of AI usage appeal particularly to younger generations, it is hypothesized that students’ decisions to misuse AI in academic contexts may also be influenced by peer pressure. This study aims to examine the roles of perceived ease of use of AI and peer pressure on academic dishonesty among first-year college students, with particular attention to AI misuse in academic activities. A total of 396 first-year students was recruited through convenience sampling. Hierarchical Regression Analysis revealed that both peer pressure and perceived ease of use of AI jointly influence academic dishonesty, particularly in the misuse of AI. However, peer pressure demonstrated a uniquely significant partial contribution to predicting dishonest behavior. These findings suggest that external social factors, particularly peer influence, play a critical role in encouraging academic dishonesty involving AI.